A Low‐Cost Metal‐Free Photocatalyst Based on Black Phosphorus. Issue 1 (9th November 2018) - Wen, Min; Wang, Jiahong; Tong, Ruifeng; Liu, Danni; Huang, Hao; Yu, Ying; Zhou, Zhang‐Kai; Chu, Paul K.; Yu, Xue‐Feng
Abstract: An efficient metal‐free photocatalyst composed of black phosphorus (BP) and graphitic carbon nitride (CN) is prepared on a large scale by ball milling. Using economical urea and red phosphorus (RP) as the raw materials, the estimated materials cost of BP/CN is 0.235 Euro per gram. The BP/CN heterostructure shows efficient charge separation and possesses abundant active sites, giving rise to excellent photocatalytic H2 evolution and rhodamine B (RhB) degradation efficiency. Without using a co‐catalyst, the metal‐free BP/CN emits H2 consistently at a rate as large as 786 µmol h −1 g −1 and RhB is decomposed in merely 25 min during visible‐light irradiation. The corresponding electron/hole transfer and catalytic mechanisms are analyzed and described. The efficient metal‐free catalyst is promising in visible‐light photocatalysis and the simple ball‐milling synthetic method can be readily scaled up. Abstract : Metal‐free black phosphorus/graphitic carbon nitride (BP/CN) heterostructures are prepared by ball milling using economical urea and red phosphorus as the raw materials. Without using a co‐catalyst, BP/CN emits H2 consistently at a rate as large as 786 µmol h −1 g −1 and rhodamine B is decomposed in merely 25 min, demonstrating excellent performances in visible‐light photocatalysis.